A field study of management stress in reindeer (Rangifer tarandus L) - Rehbinder, C.; Edqvist, L-E.; Lundström, K.; Villafane, F. (Rangifer, 1982)
The impact of stress was studied in semidomesticated reindeer subjected to various herding and handling methods. In herded and handled animals, stress lesions were found, such as abomasal haemorrhage, muscular and myocardial degeneration and marked changes in blood constituents. The degree of change was dependent of the magnitude of stress the animal had been exposed to. Manual handling and restraint was found to be one of the major stress factors. There were evident indications of a cumulative effect of repeated stress events. The use of motor vehicles (helicopter and snow-scooter), for herding and transporting the animals, was found to be an important stress factor. It is concluded that various herding and handling methods studied in the present investigation led to varying degrees of deleterious effects on the health of the animals and a poorer meatquality from slaughtered animals. Hence herding should be undertaken as carefully as possible, the time taken for manual handling should be minimized, and the corrals be so constructed as to cause a minimum of disturbance, capture and restraint. Transportation should be undertaken very cautiously with as little manual handling as possible during loading and unloading. To obtain a good meat quality, animals to be slaughtered should be subjected to a minimum of handling, i.e. slaughter should take place as quickly as possible. Transportation of live animals to slaughterhouses and the keeping of animals in corrals, pens or crates whilst awaiting slaughter will result in a lowered meat quality and should therefore be avoided.En fåltstudie av stress hos ren i samband med olika hanteringsformer.Abstract in Swedish / Sammanfatning: Betydelsen av stress hos ren studerades i hjordar i vilka olika typer av samlings- och hanteringsmetoder anvandes. I samtliga hjordar som utsatts for olika former av drivning forelag hos slaktdjur skador betingade av stress i form av magblodningar, muskelsonderfall och forandringar i blodbilden. De funna skadorna och forandringarna var beroende av den grad av stress som djuren utsatts for. Manuell hantering och inskrankning av djurens rorelsefrihet befanns vara en av de huvudsakliga stressfaktorerna. Det forelag åvenledes en stark indikation på en kumulativ effekt av upprepad stress. Anvandning av motorfordon (helikopter, snoskoter) vid drivning samt vågtransport av levande djur befanns vara betydande stressfaktorer. Det kan fastslås att de olika hanteringsformerna inneburit olika grader av stress. Graden av stresspåverkan innebår olika grader av negativa effekter dels allmånt for djurens hålsotillstånd dels for en forsåmrad kottkvalitet. Sålunda bor drivningar foretagas så forsiktigt som mojligt och tiden for manuell hantering goras så kort som mpjlig. Dårtill bor gårdor konstrueras så att yttre storning, manuell hantering och begrånsning av djurens rorelsefrihet minimeras. Transporter bor genomforas med forsiktighet och med undvikande av manuell hantering vid lastning och lossning. Slakt bor foretagas omedelbart, dvs vid gårdan. Transport av levande djur, samt hållandet av djur i gårdor eller fillor i vantan på slakt innebår att kottkvaliteten forsåmras och bor således undvikas.Kenttâtutkimus porojen stressistâ erilaisten kâsittelymuotojen yhteydessà.Abstract in Finnish / Yhteenveto: Stressin merkitystâ poroissa tutkitaan laumoissa, joissa kàytetààn erilaisia kokoamis - ja kàsittelymenetelmià. Kaikissa laumoissa, jotka olivat joutuneet alttiiksi erilaisille ajomuodoille, oli teuraselàimissâ stressin aiheuttamia vammoja mahaverenvuotojen, lihasrappeutumien ja verikuvan muutosten muodossa. Lôydetyt vammat ja muutokset olivat stressin aiheuttamat siina suhteessa kuin elaimet olivat siihen joutuneet. Kàsin pitely ja elàinten liikuntavapauden rajoittuminen havaittiin olevan yksi pààsiallisista stressintekijôistà. Oli esillà myôs voimakas osoitus kasvavan vaikutuksen toistuvasta stressistâ. Moottoriajoneuvojen (helikopteri, moottori-kelkka) kàyttô ajossa sekà elàvien elàinten tiekuljetus nayttivàt olevan merkittàvià stressitekijôità. Voidaan todeta, ettà erilaiset kasittelymuodot ovat aiheuttaneet stressin erilaisia asteita. Stressin vaikutuksen taso aiheutti eri asteisia negatiivisia vaikutuksia osittain huonontuneeseen lihan laatuun. Nainollen pitàà ajot suorittaa niin varovaisesti kuin mahdollista ja aika kàsin pitelyyn tehtàvà niin lyhyeksi kuin mahdollista. Sen lisàksi pitàà aidât rakentaa niin, ettà ulkoista hàirintàà, kàsin pitelyà ja elàinten liikuntavapauden rajoitusta vàhennetààn. Kuljetukset pitàà suorittaa varovaisuudella ja koettaa vàlttàà kàsin pitelyà kuormauksessa ja purkauksessa. Teurastaminen pitàà suorittaa vâlittômàsti, toisin sanoen aidan luona. Elàvien elàinten kuljetus, sekà elàinten pitàminen aitauksissa tai tarhoissa teurastamista odotellessa aiheuttaa lihalaadun huonontumiseen ja pitàà nàin ollen vàlttàà.